Seismic Interpretation Using RMS Amplitude and Envelope Attributes to Identify Hydrocarbon Prospects in the “CAT” Field, Central Sumatra Basin - Sulaiman, Ryan; Adhi, M. Aryono; Nurcahya, Budi Eka (Universitas Negeri Semarang, 2023)
To enhance oil production rates, optimising idle wells with reserve potential and continuing exploration efforts to discover new hydrocarbon resources are necessary. The CAT Field in the Central Sumatra Basin is one of Indonesia's prospective oil and gas-producing areas. This study aims to identify and map the distribution of sandstone reservoirs through 3D seismic data interpretation using RMS Amplitude and Envelope seismic attributes. The data used are secondary data from a reflection seismic survey processed at the Energy Study Centre. The interpretation stages include well-to-seismic tie, horizon picking, time structure mapping, and seismic attribute analysis. The interpretation results show that RMS Amplitude values in the Duri Formation range from 0.80 to 5.60, while in the Bekasap Formation, they range from 0.00 to 4.00. The Envelope attribute values in the Duri Formation range from 0.60 to 8.40, and from 0.50 to 6.00 in the Bekasap Formation. High attribute value zones are consistently detected around wells CAT_01, CAT_03, and northwest of CAT_02, corresponding to elevated topography based on the time structure map. These findings indicate potential hydrocarbon accumulation in the area, making it a prime target for field development and revitalisation. Seismic attribute interpretation offers an efficient exploration approach and supports future sustainable exploration efforts.